Effectiveness of Diclofenac and Paracetamol Infusion for Post-operative Pain Relief in Total Abdominal Hysterectomy under Subarachnoid Block - A Comparative Study - Omprakash Sundrani; Durga Shankar Patel; Anand Masih Lakra; Kishor Kumar Som; Kamal Kishore Sahare (Academia Anesthesiologica International, 2019)
Background: Aim: To compare the effectiveness of the diclofenac and paracetamol infusion for post operative pain relief in Hysterectomy patient under subarachnoid block in 24 hours.Subjects and Methods:This prospective randomized, clinical study was performed on 100 female patients belonging to American Society of Anesthesiologists grade I/II, aged 40-60 years of age undergoing hysterectomy  under Subarachnoid block. These patients were divided in to two Groups A and B with 50 patients in each according to drug given for postoperative analgesia that is diclofenac75mg  andparacetamol 1000mg respectively. Pain was assessed by VAS at the completion of infusion for effective analgesia (VAS<3). If patient did not achieve effective analgesia than rescue analgesia was provided with fentanly 20 mcg.Results:IV diclofenac 75 mg 12 hourly and paracetamol 1000 mg 6 hourly provides effective post operative pain relief. Paracetamol regimen shows better effect  thandiclofenac in 24 hours post operative period. Rescue analgesia with fentanyl 20mcg provides quick and effective pain relief in moderate to severe breakthrough pain in post hysterectomy patients.Conclusion: IV Paracetamol is superior in terms of effectiveness of pain relief and rescue analgesia required. Common side effect comprising of nausea, vomiting, pruritis were observed in few no of cases. No patients required special treatment. No serious side effect like hypotension, respiratory depression, bleeding, allergic reactions were observed.